Growth Responses of Red-Leaf Lettuce to Temporal Spectral Changes - Meng, Qingwu; Runkle, Erik S. (Frontiers in Plant Science, 2020)
Lighting is typically static for indoor production of leafy greens. However, temporal spectrum differentiation for distinct growth phases can potentially control age-specific desirable traits. Spectral effects can be persistent yet dynamic as plants mature, necessitating characterization of time-dependent responses. We grew red-leaf lettuce (Lactuca sativa L.) ‘Rouxai’ in a growth room at 23 °C and under a 20-h photoperiod created by warm-white (WW), blue (B; peak = 449 nm), green (G; peak = 526 nm), red (R; peak = 664 nm), and/or far-red (FR; peak = 733 nm) light-emitting diodes. From day 0 to 11, plants received six static lighting treatments with the same total photon flux density (400–800 nm): WW180, R180, B20R160, B20G60R100, B20R100FR60, or B180 (subscripts denote photon flux densities in µmol∙m–2∙s–1). On day 11, plants grown under each of the six treatments were transferred to all treatments, which created 36 temporal spectrum alternations. Plant growth, morphology, and coloration were measured on days 11 and 25. Increasing B radiation from 0 to 100% in static treatments decreased shoot fresh and dry weights and increased foliage redness of seedlings and mature plants. Compared to B20R160, B20R100FR60 increased shoot fresh weight, but not dry weight, on both days. However, other phenotypic responses under static treatments changed over time. For example, leaf length under B180 was 35% lower on day 11 but similar on day 25 compared to that under R180. In the B20 background, substituting G60 for R radiation did not influence shoot weight on day 11 but decreased it by 19% on day 25. When plants were switched from one treatment to another on day 11, the treatments applied before day 11 influenced final shoot weight and, to a lesser extent, leaf length and foliage coloration on day 25. In comparison, effects of the treatments applied after day 11 were more pronounced. We conclude some phenotypic responses to light quality depend on time and sequential light quality treatments had cumulative effects on lettuce growth. The temporal complexity of spectral responses is critical in photobiological research and creates opportunities for time-specific spectrum delivery to optimize crop characteristics.